2018
DOI: 10.1155/2018/2708491
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Interval Training Regulated SIRT3 Attenuates High-Fat-Diet-Associated Cognitive Dysfunction

Abstract: Cognitive dysfunction is an important complicated disease in obesity. Exercise ameliorates obesity and the related cognitive dysfunction. However, the underlying mechanism is still unclear. In this study, we investigated whether aerobic interval training (AIT) could attenuate high-fat-diet- (HFD-) associated cognitive dysfunction and the possible mechanism of SIRT3-MnSOD pathway. C57BL/6 wild-type (WT) mice and SIRT3 knockout (KO) mice were randomized into control (Con) or HFD group with or without AIT trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…However, aerobic interval training attenuated neuronal apoptosis and improved cognitive function in mice with HFD through the positive regulation of the SIRT3-MnSOD pathway, and the reduction of oxidative stress levels. These findings would place SIRT3 as a new factor in the neuroprotective field [18].…”
Section: Skeletal Muscle Sirtuins and Exercisementioning
confidence: 99%
“…However, aerobic interval training attenuated neuronal apoptosis and improved cognitive function in mice with HFD through the positive regulation of the SIRT3-MnSOD pathway, and the reduction of oxidative stress levels. These findings would place SIRT3 as a new factor in the neuroprotective field [18].…”
Section: Skeletal Muscle Sirtuins and Exercisementioning
confidence: 99%
“…According to the evidence on the neuroprotective effect of SIRT3 during exercise, Shi and colleagues demonstrated that aerobic interval training (AIT)-induced SIRT3 expression decreased OS generated by HFD, thereby improving cognitive function [55]. The authors reported that HFD significantly compromised cognitive function in mice and particularly in SIRT3-deficient mice [55], remarking that alterations in glucose and lipid metabolisms are noxious for vital organs. Moreover, HFD increased acetylation levels of several proteins in the hippocampus; among those, MnSOD became iper-acetylated and was unable to blunt ROS production [55].…”
Section: Sirtuin Modulation and Physical Activitymentioning
confidence: 99%
“…The authors reported that HFD significantly compromised cognitive function in mice and particularly in SIRT3-deficient mice [55], remarking that alterations in glucose and lipid metabolisms are noxious for vital organs. Moreover, HFD increased acetylation levels of several proteins in the hippocampus; among those, MnSOD became iper-acetylated and was unable to blunt ROS production [55]. Subsequently, mice fed with HFD were subjected to AIT for 6 weeks, showing an increase in SIRT3, which, in turn, deacetylated MnSOD and reduced OS [55].…”
Section: Sirtuin Modulation and Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sport exercises, like the CR, reduce overweight, obesity, and related disorders by activating countless signaling pathways. In a study, Shi et al stated that interval training by regulating sirtuin-3 (SIRT3) could reduce the cognitive dysfunction associated with HFD (20). Physical activity is also recognized as an effective method for improving the cognitive function of all age groups, especially the elderly who are more susceptible to neurological disorders since the release of mycoses by the operating muscles leads to the upregulation of neurotrophin expression in the hippocampal dentate gyrus (12).…”
Section: Discussionmentioning
confidence: 99%